Build Design Of Electric Bike As Energy Efficient Transportation - Sundhy Pareza; Purwantono Purwantono; Remon Lapisa; Primawati Primawati (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
The issue of global warming is very strong in the force in the procession, the damage caused by global warming is very influential in the survival of living beings. The methods performed in this study are experimental methods. The experiments performed were to make a design and to become a unity so that it formed a tool of electric bicycle transportation that can be used well. This thesis author devise and assemble electric bicycle using DC electric motor 24 Volt 250 Watt and 3000 rpm. The power system used is 24 Volt 12 Ampere battery. From the results of the test and analysis of data that has been taken on the electric bicycle obtained data of the average speed obtained by the electric bike with a load of 78 = 4.94 m/s, load 83 = 4.59 m/s, load 88 = 4.25 m/s, power output to drive electric bicycle with load 78 = 266.679 Watt, load 83 = 263.810 Watt, load 88 = 258.984 Watt. Isu pemanasan global sangat kuat di gencar disuarakan, kerusakan yang disebabkan pemanasan global sangat berpengaruh pada kelangsungan hidup makluk hidup. Metode yang dilakukan dalam penelitian ini adalah metode eksperimen. Eksperimen yang dilakukan adalah membuat sebuah rancangan dan merakitnya menjadi suatu kesatuan sehingga terbentuk sebuah alat transportasi sepeda listrikyang dapat digunakan dengan baik. Skripsi ini penulis merancang dan merakit sepeda listrik dengan menggunakan motor listrik DC 24 Volt 250 Watt dan 3000 rpm. Sistem daya yang digunakan adalah baterai 24 Volt 12 Ampere. Dari hasil pengujian dan analisis data yang telah diambil pada sepeda listrik didapatkan data berupa kecepatan rata-rata yang didapatkan sepeda listrik dengan beban 78 = 4,94 m/s, beban 83 = 4,59 m/s, beban 88 = 4,25 m/s, daya output untuk menggerakkan sepeda listrik dengan beban 78 = 266,679 Watt, beban 83 = 263,810 Watt, beban 88 = 258,984 Watt.